Parents and teachers’ characteristics as predictors of reading self-efficacy of students with learning disabilities in Ibadan Oyo state, Nigeria (2019)
The study investigated the predictions of teachers’ characteristics and parents’ characteristics to reading self-efficacy of students with learning disabilities in junior secondary schools in Ibadan North Local Government Area, Oyo State. The study adopted a descriptive research design. A sample of one hundred (100) students with learning disabilities was purposively selected from four (4) sampled junior secondary schools. Three validated research instruments titled: Screening Checklist for Suspected Learning Disabilities (r=0.72), Teacher and Parent Factors Questionnaire (r= 0.73) and Students’ Reading Self-Efficacy Questionnaire (r = 0.85) were used for data collection. The data collected were subjected to analysis with the use of Pearson product moment correlation and multiple regressions. Results revealed that parents’ verbal support and encouragement of their children (r = 0.265, p(0.161)<0.05) and parents’ socio-economic status (r=.239, p(0.016)0.05) have significant positive relationship with reading self-efficacy of the participants while teachers’ use of reinforcement and teachers’ level of education have no relationship with reading self-efficacy of the participants. The independent variables combined together accounted for 12.4% of the variance in the prediction of the reading self-efficacy of the participants. The analysis of variance for the regression yielded an F-ratio of 3.361 significant at 0.05 level. Results obtained also showed that parents’ verbal support and encouragement of their children ((3 = 0.256) and parents’ socio-economic status (p = 0.216) have positive contributions to reading self-efficacy of participants while teachers’ use of reinforcement and teachers’ level of education did not account for variability in the dependent variable. It is therefore recommended that school administrators and teachers should ensure that they educate parents of students with learning disabilities on the need to provide adequate verbal support and encouragement to their wards in order to improve the students’ reading self-efficacy.